Analysis of the dynamics of changes in factor load models for predicting failures of a spacecraft - Kraev Konstantin; Zaitsev Pavel; Kazakovtsev Vladimir (ITM Web of Conferences)
The paper considers the theoretical aspects of factor analysis as applied to the problem of predicting the failure-free operation of low-orbit communication satellites. The authors described the nature of the factors affecting the spacecraft during operation. The structure of the methodology for preparing data and creating factor load models is described. A methodology for analyzing the dynamics of changes in factor load models is proposed. The basic concepts and the algorithm are described. A numerical experiment to test the proposed hypothesis and interpreted the key factors influencing the functioning of the spacecraft is described. The factors are distributed into influence groups. As a result of the numerical experiment and the conducted analysis of the dynamics of changes in the factor load models, we made a conclusion on the validity of the proposed hypothesis. The practical applicability of the described approach for predicting failures and malfunctions during the operation of spacecraft is discussed.